2016
DOI: 10.1186/s12929-016-0260-5
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid synergically enhances BMP2-induced bone formation via stimulating Smad 1/5/8 and p38 pathways

Abstract: BackgroundHealing of bone defects is a dynamic and orchestrated process that relies on multiple growth factors and cell types. Bone morphogenetic protein 2 (BMP2) is a key growth factor for bone healing, which stimulates mesenchymal stem cells to differentiate into osteoblasts. Betulinic acid (BetA) is a natural pentacyclic triterpenoid from plants. This study aimed to examine combinatory effects of BetA and BMP2 on ectopic bone generation in mice.ResultsIn MC3T3-E1 preosteoblast culture, 10–15 μM of BetA incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Moreover, our study further demonstrated the effects of SMAD5-AS1 and miR-195 on the BMP2/SMAD5 pathway. The translocation of pSMAD5 from the cytoplasm to the nucleus can be stimulated by BMP2 (20). Consistently, BMP2 overexpression was determined to stimulate the phosphorylation of SMAD5 in this study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, our study further demonstrated the effects of SMAD5-AS1 and miR-195 on the BMP2/SMAD5 pathway. The translocation of pSMAD5 from the cytoplasm to the nucleus can be stimulated by BMP2 (20). Consistently, BMP2 overexpression was determined to stimulate the phosphorylation of SMAD5 in this study.…”
Section: Discussionsupporting
confidence: 79%
“…Bone morphogenetic protein 2 (BMP2), as a stimulator of the SMAD5 pathway (20), is reported to accelerate NPC cell migration and invasion as well as to induce EMT (21,22). We subsequently intended to explore whether the role of SMAD5-AS1/miR-195 in NPC was related to the BMP2/SMAD5 pathway.…”
Section: Silencing Of Smad5-as1 or Elevation Mir-195 Impairs Npc Cellmentioning
confidence: 99%
“…As a member of the SLRP family, BGN can coordinate with the transforming growth factor β (TGF-β) superfamily members to modify TGF-β/BMP activities and functions (Hildebrand et al, 1994 has been reported to be highly expressed in the developing flexor tendon and has positive effects on tendon repair (Macias et al, 1997;Mihelic et al, 2004). Consistent with that, in our study, we found that BMP7 strongly increased in the TDSCs that were It has been reported that BMP2 enhanced bone formation and osteoblast differentiation via stimulating Smad1/5/8 (Choi, Jeong, Kook, & Koh, 2016). It remains unclear why the activation of the same pathway results in different cellular responses.…”
Section: Discussionsupporting
confidence: 90%
“…Several therapeutic agents such as betulinic acid have also been implicated in immune reconstitution and the reversal of ATI. These agents possess pharmacological properties that improve the cellular as well as humoral immunity (Choi et al 2016;Jine et al 2012;Mullauer et al 2010). Treatment with these agents enhances the total number of thymocytes, thus causing an increase in the thymus weight index (Yi et al 2010), and has a protective effect against DM-induced thymocyte apoptosis in mice (Yi et al 2016).…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%